1993
DOI: 10.1007/bf00449431
|View full text |Cite
|
Sign up to set email alerts
|

The importance of quality of life research for health care reform in the USA and the future of public health

Abstract: Quality of life research data have significant implications for the social and public policy in the USA as it can be used to evaluate the cost-effectiveness of various permutations of treatment as well as the 'human effectiveness' of health care system restructuring. The USA spends more on health care per capita than any other industrialized nation, yet on major health indicators, such as infant mortality rate, this expenditure is not related to beneficial effects on the community. When epidemiological and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…This shift in perspective went simultaneously with an increased demand towards measuring the effectiveness of health care [3]. Taking this together, this highlights the importance of measuring HRQoL in today’s health care [4]. …”
Section: Introductionmentioning
confidence: 99%
“…This shift in perspective went simultaneously with an increased demand towards measuring the effectiveness of health care [3]. Taking this together, this highlights the importance of measuring HRQoL in today’s health care [4]. …”
Section: Introductionmentioning
confidence: 99%
“…In the case of Dentistry and its allied subspecialties, such as Orthodontics the confidence in technology (complex therapeutic techniques and highly advanced diagnostic resources) needs to be mitigated, as public health services must be in motion towards less costly and uncomplicated health care alternatives, providing appropriate counseling about the negative effects of malocclusion and guaranteeing preventive measures to deal with occlusal and skeletal alterations to as many users as possible and as timely as feasible. 30 In this regard, public health policies should be tailored for the appropriate Severe malocclusion negatively impacts adolescents' QoL Bretz et al…”
Section: Discussionmentioning
confidence: 99%
“…The literature urges that healthcare services encourage communication among the provider, the patient and his/her guardians. If it happens otherwise, with epidemiology 28 and the concept of quality of life 30 failing to orient public health initiatives, health care expenditures will rise and public health services may suffer unprecedented challenges. For further research, more in-depth studies on malocclusion among adolescents and its association with bullying are suggested, since few publications on this topic have been found in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concepts as Health, Quality of Life and Health Related Quality of Life, have gained, in the last decades, a great importance in regard to the assessment of treatment outcomes and expectations, as well as patients' selfperception [1]. According to the definition given by the World Health Organization, Health is a state of complete physical, mental, and social well-being and not merely the absence of disease or infirmity [2].…”
mentioning
confidence: 99%